Local acceleration of coastal flood risk in response to relative sea level change - Ryan Paulik; Rebecca Welsh; John Powell (Scientific Reports)
Abstract Coastal communities are expected to experience an increased episodic flooding threat as sea levels rise during the 21st century. While global sea level rise (SLR) is a significant contributor, local processes such as vertical land motion (VLM) influence the flooding threat timing and magnitude. This study estimated building financial losses for extreme sea level-driven flooding and relative sea level (RSL) change in New Zealand. Financial losses were calculated for individual building objects over a future 100-year period using SLR projections for medium confidence Shared Socio-economic Pathway (SSP) scenarios 2–4.5 and 5.8–5, with local VLM. Local VLM increased national 100-year coastal flooding losses by up to 15% at 2100 compared to SLR alone, and bringing forward the expected end-of-century losses by 10–12 years. At subnational levels, annual losses between 2050 and 2100 could occur up to 25 years earlier from downward land motion and 19 years later from upward motion. These findings highlight the importance of including VLM in coastal flood risk assessments to inform risk mitigation location and timing under changing RSLs.